Dermal exposure to pesticides among sprayers in different agriculture subsectors in Malaysia: observational method using DREAM - Mustafa Udin, Nurulain; Syed Ismail, Sharifah Norkhadijah; How, Vivien; Zainal Abidin, Emilia (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: An assessment of dermal exposure to pesticide mixtures among sprayers was made as a function of crop type, in four agricultural subsectors in Malaysia. Methods: The potential and actual dermal exposures for 160 pesticide sprayers performing pesticide spraying task were estimated by using Dermal Exposure Assessment Method (DREAM). Results: Results showed that there was significant difference between nationality (p<0.001), highest education (p<0.001), monthly income (p=0.002), body mass index (p<0.001) and smoking habit (p<0.001) distributions of sprayers in different agriculture subsectors. Various types of pesticides were used by respondents, where class II (moderately hazardous) and class III (slightly hazardous) pesticides were the most frequently used pesticides. There was a significant difference in both tPDE (χ2 = 118.093, p<0.001) and tADE (χ2 = 84.980, p<0.001) between different agricultural sectors, where the prominent high tPDE was observed among paddy pesticide sprayers (151.39 ± 22.64 DU) while lowest exposure was recorded among oil palm plantation sprayers (47.67 ± 18.47 DU). Conclusion: Based on DREAM exposure categories, majority of the pesticide sprayers (68.9%) working in paddy farming were exposed in low dermal exposure while 26.7% of respondents were exposed to moderate exposure. Pesticide sprayers in other agriculture sectors were exposed to very low to low exposure level. Dermal exposure distributions on body parts were varied between sectors, influenced by several factors such as crop type, height, and spraying methods.